FAKTOR-FAKTOR YANG MEMPENGARUHI STRES KERJA DAN PENGENDALIAN STRES KERJA PADA TENAGA KERJA DI BAGIAN CARGO PT. ANGKASA PURA LOGISTIK BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Utami, Putri; Wahyuni, Ida; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Work stress is a feeling of pressure or distress experienced by employees in the face of job. In carrying out activities in each group, humans can encounter a stress. The same condition also occurs to a workers in cargo section in doing his task. This research used mix method approach (quantitative – qualitative). The subject of the research is the workers in cargo section PT Angkasa Pura logistik Semarang. The data were collected by spreading the questionnaire of work stress symptoms on 47 respondent, 54,1% experienced severe labor stress, 45,9% experienced mild stress and 0% did not experience work stress. Based on eight job stress factors studied, the intrinsic factors of the job (job demands and work environment) and external job demands all the elements related to work stress a workers in cargo section PT Angkasa Pura logistik Semarang (subjectively).How to control work stress on the workers in the cargo section that does not experience work stress in controlling the saturation is by joking with co-workers play mobile phones and always try to stay focused. If there is a problem at work or with colleagues, they discuss with the Leader and colleagues to find the best solution. To relieve fatigue during work is by drinking body movements and cool the body in the customer service.